Functional Diversities of Regulatory T Cells in the Context of Cancer Immunotherapy - Gao, Ran; Shi, Guo-Ping; Wang, Jing (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) are a subset of CD4+ T cells with their immunosuppressive activities to block abnormal or excessive immune responses to self and non-autoantigens. Tregs express the transcription factor Foxp3, maintain the immune homeostasis, and prevent the initiation of anti-tumor immune effects in various ways as their mechanisms to modulate tumor development. Recognition of different phenotypes and functions of intratumoral Tregs has offered the possibilities to develop therapeutic strategies by selectively targeting Tregs in cancers with the aim of alleviating their immunosuppressive activities from anti-tumor immune responses. Several Treg-based immunotherapeutic approaches have emerged to target cytotoxic T lymphocyte antigen-4, glucocorticoid-induced tumor necrosis factor receptor, CD25, indoleamine-2, 3-dioxygenase-1, and cytokines. These immunotherapies have yielded encouraging outcomes from preclinical studies and early-phase clinical trials. Further, dual therapy or combined therapy has been approved to be better choices than single immunotherapy, radiotherapy, or chemotherapy. In this short review article, we discuss our current understanding of the immunologic characteristics of Tregs, including Treg differentiation, development, therapeutic efficacy, and future potential of Treg-related therapies among the general cancer therapy.